The SAGE glossary of the social and behavioral sciences - Sullivan, Larry E. (Los Angeles, [Calif.] ; London : SAGE, 2009)
Covering both print and electronic formats, this curriculum-driven A-Z of the major terms in social and behavioural sciences spans anthroplogy, communication and media studies, criminal justice, economics, education, geography human services, management, political science, psychology and sociology.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Social sciences -- Dictionaries; Psychology -- Dictionaries